Onyx storm [compact disc, unabridged] - Yarros, Rebecca (Yarros, Rebecca. Empyrean., 2025)
After months at Basgiath War College, Violet Sorrengail knows there is no more time for lessons because the battle has truly begun. With enemies coming from outside and within their ranks, she must go on a journey to seek allies from unfamiliar lands. The trip will be grueling, but she will do anything to save her dragons, her family, her home, and him.